The deliberative democracy handbook : (Jossey-Bass, 2005)
The Deliberative Democracy Handbook is a terrific resource for democratic practitioners and theorists alike. It combines rich case material from many cities and types of institutional settings with careful reflection on core principles. It generates hope for a renewed democracy, tempered with critical scholarship and political realism. Most important, this handbook opens a spacious window on the innovativeness of citizens in the U.S. (and around the world) and shows how the varied practices of deliberative democracy are part of a larger civic renewal movement.